Present status of using aqua medicines and chemicals on fish health management in Bogura district, Bangladesh - Akter, Mst Nahid; Sarker, Gobindo; Ali, Md Mozahar; Zafar, Md Abu (Research in Agriculture Livestock and Fisheries, 2020)
In order to understand the existing status of aqua-medicines and chemicals in aquaculture activities present investigation was conducted from January to June 2017 in four upazilas of Bogura district namely, Bogura Sadar, Sherpur, Kahaloo and Shibganj. Questionnaire and focus group discussion were used for data collection. Among the latest aquachemicals, geotox, jv zeolite, mega plus, aquastar pond, acme's zeolite, zeo-fresh, aqua green, biomin pond life, aquakleen, megagio gold, and aqua boost were extensively used. Probiotics like profs, aqua photo, aqua gold, super biotic and pond care were used. The selected farmers used growth promoter such as saltose, panvit aqua, spa gelly, aqua boost and bio-pond, bio-grow, aqua pure, gasstrap, metrix, geo-rich bio-aqua 50 and aqua magic were used as toxic gas reducer. Approximately 11 trade names of antibiotics were marketed in the selected area. Their main active ingredients were chlortetracycline, oxytetracycline, amoxicillin, co-trimoxazole, azithromycin and sulphadiazine. The survey identified some problems connected with the practice of such chemicals such as shortage of fish farmer’s knowledge about the usage of chemicals, proper dosage and their maintenance. Res. Agric., Livest. Fish.7(1): 129-138, April 2020